Policy review and institutional analysis of the hydropower in Laos - Suhardiman, Diana; de Silva, Sanjiv; Carew-Reid, Jeremy (IWMI, ICEM, CPWF, 2011)
The   report   reviewed   existing   policies   and   legal   frameworks   relating   to   land-‐water-‐environment   management   with   a   focus   on   hydropower   development   and   livelihood   options   in   Lao   PDR,   Cambodia,   and  Vietnam.  It  described  and  analyzed  the  sectoral  decision-‐making  set  up  at  national  level.  Later,  this   decision-‐making  set  up  was  linked  with  operational  rules  and  procedures  of  hydropower  projects  in  each   of  the  three  countries.